Pengaruh Media Pembelajaran Flashcard Terhadap Kemampuan Menulis Surat Dinas Siswa Kelas VII SMP Muhammadiyah 1 Medan - Zuhriah Umi Kalsum; Khairil Ansari (Jurnal Pendidikan, Bahasa dan Budaya, 2023)
This study aims to, (1) To describe the ability to write official letters of VII grade students of SMP Muhammadiyah 1 Medan in the academic year 2022/2023 before using flashcards learning media. (2) To describe the ability to write official letters of VII grade students of SMP Muhammadiyah 1 Medan in the academic year 2022/2023 after using flashcard learning media. (3) To describe the impact of using flashcard learning media in improving the ability to write official letters of VII grade students of SMP Muhammadiyah 1 Medan in the academic year 2022/2023. The population in this study were all VII grade students of SMP Muhammadiyah 1 Medan with a research sample of 37 students of VII-T2 grade students of SMP Muhammadiyah 1 Medan. The instruments used in this study are the accuracy of letter content, completeness of letter content, appropriateness of letter format, word accuracy, sentence accuracy, and spelling and writing. The method used in this research was one group pretest-posttest. The data analysis technique used the analysis requirement test, normality test, and hypothesis testing. The results of pretest research obtained an average of 57.75, and fell into the category of less. However, the posttest research results obtained an average of 79.29 and included in the good category. Through hypothesis testing, namely 6.20057 > 2.02809, it can be concluded that there is a significant effect of flashcard learning media on the ability to write official letters of VII grade students of SMP Muhammadiyah 1 Medan.